The Implication of E-commerce Emerging Markets in Post-Covid Era - Ahmed, Nasif; Kumari, Akriti (International Journal of Entrepreneurship and Business Management, 2022)
The process of buying and selling via internet platforms is referred to as E-commerce. E-commerce has become a worldwide trend in recent years. People from all around the world have begun to purchase things online. Mobile commerce, money transfer, inventory management, and other aspects of electronic commerce are included. With only a few clicks, anyone can send anything to anyone, whether it's money or presents. In the future, electronic commerce might have a significant economic impact. Internet business will permanently alter the face of business. Furthermore, in the twenty-first century, E-commerce will transform banking. E-commerce has had a wide range of effects on the increasing global economy. First and foremost, it has impacted information technology and all economic sectors; above all, E-commerce has boosted global productivity growth and its impact are too high. They are able to determine the number of qualified people required to advance their country's information economy, as well as calculate the amount of investment required to provide businesses with internet access. Some benefits are now in a position to compare their economies to those of their international competitors, and there are numerous ways to boost productivity growth in present emerging markets.